Correlação entre a composição química de cones de guta-percha e sua qualidade obturadora de canais radiculares: avaliação de diferentes marcas comerciais - Silva Júnior, João Batista Araújo (2003)
The chemical composition of eight commercially available of gutta-percha cones brands was determined and the results correlated with the apical seal ability. These brands were: (AnalyticÔ, DentsplyÔ, DiadentÔ, MetaÔ, ObturaÔ, OdusÔ, TanariÔ and UltimateÔ). The gutta-percha cones components (ZnO, BaSO4, gutta-percha, wax and resins) were initially obtained by Frideman et al 38 method. The composition of cones was obtained by gravimetric analysis, energy-dispersive X-ray microanalysis, X-ray diffraction and elemental analysis. The gutta-percha polymer was characterized by thermal analysis (TGA and DSC), intrinsic viscosity, gel permeation chromatography, infrared and nuclear magnetic resonance. The method described by Friedman et al 38 was appropriated to quantify gutta-percha and resin/wax components of cones, but led to overestimation of barium sulphate and zinc oxide. An average increase in the amount of barium sulfate of 3.5% in relation to the corrected BaSO4 mass value and of 43.6% in relation to cone mass was observed. Gutta-percha content range from 14.5 to 20.4% and zinc oxide from 62.8 to 84.3%. Barium sulphate was not detected in three of these brands (DentsplyÔ, OdusÔ and TanariÔ). TGA analysis shows that the inorganic residue obtained in this technique is similar of the inorganic residues observed in the gravimetric analysis. Crystal phases of gutta-percha polymer were identified by DSC. AnalyticÔ, DiadentÔ, MetaÔ, ObturaÔ, OdusÔ and TanariÔ brands presents endothermic peak characteristic of b-guttapercha. In the other two brands the polymer is present in the a-phase. Molar mass determination by viscometric analysis shows similar values of seven brands in the average of 1.0 x 105 to 1.6 x 105 g/mol, however the polymer present in the TanariÔ brand has lower molar mass (5.6 x 104 g/mol). Similar results were obtained by GPC. 11 The polymer present in the eight brands were analysed by IV and NMR, transpolyisoprene was identified as the main polymer component in the gutta-percha cones. The infiltration results of five brands (DentsplyÔ, TanariÔ, ObturaÔ, OdusÔ and AnalyticÔ ) indicates that the small amount of gutta percha and also the presence of the a-phase in the DentsplyÔ brand may be responsible for the high infiltration observed. A poor sealing ability was observed for brands with gutta-percha content lower than 16%.